Pemahaman Politik dan Identifikasi Kepartaian Perempuan dalam Pemilu 1999 di Kota Padang - Rafni, Al; Suryanef, Suryanef (Jurnal Demokrasi, 2005)
This article intended to provides an explaination of how women political comprehension and their party identification in 1999 general election in Padang. The data is collected from 200 respondents by questionaire and analyzed by using quantitative descriptive method. Data finding shows majority of respondents engage to superficial political comprehension. Women political comprehension is only better in case of real political nuance such as presidential power, bureaucracy service and general election management. Meanwhile, in general, level of party identification is found rather weak which is resulted to easiness for women to being politicized. Party preferences of respondents in 1999 general election were PAN, PPP, Golkar, PK and PDI-Perjuangan in a row.